Ilham Allah dalam inneransi Alkitab - Suparyadi, Zakharia; Eppang, Paulus; Zebua, Yaterorogo; Saputro, Mihardo (Sekola Tinggi Teologi Sangkakala Jakarta, 2024)
ABSTRACTThe Bible is a book of instructions and a guide for Christians that serves to teach, reveal errors, correct behavior and educate people in the truth. The Bible consists of 39 Old Testament books and 27 New Testament books which are believed to be the Word of God. The focus of this research is the development of the results of the study of the book